(untitled) (Economics and region, 2024)
The article examines the issue of the formation of the economic potential of the enterprise and the factors influencing the process of its formation. The formation and state of the hotel enterprise’s economic potential are influenced by external and internal factors, which can be divided into the following three groups: macroenvironmental factors, microenvironmental factors, and episodic factors. The variability of the external and internal environments directly affects the development, effective and competitive activity of the hotel enterprise. The opinions of scientists regarding the structuring of the economic potential of the enterprise were studied, however, without taking into account the sectoral specificities of the activity. The priority of the components of the economic potential of the enterprise depends on the sphere and characteristics of its activity, as a driving force for strengthening positions on the market and the ability to withstand fluctuations in influencing factors. The structuring of the economic potential of a hotel enterprise is a very important aspect for its formation and successful implementation in the future, since the development or decline of one component affects the state of the potential as a whole due to the interdependence and interconnectedness of the whole system. In the conditions of destabilizing factors, it is proposed to single out the main components of the structure of the economic potential for hotel enterprises for the possibility of further determining its condition and proposals for strengthening the weak points, strengthening the strong points and managing the enterprise as a whole. Thus, the following list of components of the economic potential of the hotel industry enterprise is proposed: financial, labor, production and operation, marketing and reputational. These components fully provide an opportunity to assess the state of efficiency and competitiveness of the enterprise. The proposed components are an integral part of the economic potential in the efficient and competitive operation of the hotel business in the market of hotel services.